Assessing the role of the Automatic Identification System (AIS) in navigational safety: A case study of the General Cargo Vessel MV Guhi Mas - Tanti Diyah Rahmawati; Anak Agung Istri Sri Wahyuni; Tika Septia (Politeknik Pelayaran Banten, 2025)
Shipping safety is fundamental to the maritime industry, and navigational systems are central to safe operations. In line with IMO/SOLAS requirements, the Automatic Identification System (AIS) supports collision avoidance, ship traffic services, navigational aids, search and rescue, and accident investigation. AIS continuously broadcasts a vessel’s identity, position, course, speed, and navigational status, enabling other ships and coastal stations to track targets and anticipate risk. Integrated with ECDIS, radar, and ARPA, AIS enhances situational awareness in meeting, crossing, and overtaking situations by providing parameters such as CPA (Closest Point of Approach) and ETA (Estimated Time of Arrival). This study analyzes the role of AIS in navigational safety on a general cargo vessel (MV Guhi Mas). The findings indicate that AIS is critical to safe navigation: it improves target identification around the vessel, facilitates real-time data exchange with VTS, strengthens decision-making on the bridge, and contributes to incident prevention and post-event analysis. Regulatory carriage requirements further underscore AIS as an essential instrument for reducing maritime accidents. Keselamatan pelayaran merupakan fondasi industri maritim, dan sistem navigasi berperan sentral dalam operasi yang aman. Selaras dengan persyaratan IMO/SOLAS, Automatic Identification System (AIS) mendukung pencegahan tubrukan, layanan lalu lintas kapal, sarana bantu navigasi, pencarian dan penyelamatan (SAR), serta investigasi kecelakaan. AIS menyiarkan secara kontinu identitas kapal, posisi, haluan, kecepatan, dan status navigasi, sehingga kapal lain dan stasiun pantai dapat melacak target dan mengantisipasi risiko. Terintegrasi dengan ECDIS, radar, dan ARPA, AIS meningkatkan kesadaran situasional pada situasi berhadapan, bersilangan, dan menyalip dengan menyediakan parameter seperti CPA (Closest Point of Approach) dan ETA (Estimated Time of Arrival). Studi ini menganalisis peran AIS dalam keselamatan navigasi pada kapal general cargo (MV Guhi Mas). Temuan menunjukkan bahwa AIS krusial bagi navigasi aman: meningkatkan identifikasi target di sekitar kapal, memfasilitasi pertukaran data waktu nyata dengan VTS, memperkuat pengambilan keputusan di anjungan, serta berkontribusi pada pencegahan insiden dan analisis pascakejadian. Persyaratan pemasangan wajib dalam regulasi semakin menegaskan AIS sebagai instrumen esensial untuk menurunkan kecelakaan maritim.